La décentralisation de l'aménagement du territoire : mythe ou réalité? - Glenn, Jane (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
This paper examines the tension between centralizing and decentralizing forces in systems of land use planning. Its thesis, drawn from the LaHaye Report, is that the degree of centralization of the system is directly proportional to the breadth of jurisdiction of the planning authority. While Quebec's system of land use planning is reputed to be decentralized and political, the author questions whether this assessment is correct. The role of the government under the Land Use Planning and Development Act and other specialized legislation is more in accordance with the centralized and technocratic systems advocated in earlier Quebec proposals for land use planning. This conclusion is reinforced by a consideration of the suggestions put forward in Le Choix des régions and their present-day application.